Urgensi Pendidikan Politik di Provinsi Aceh Studi Kasus: Politik Uang dalam Pemilu di Kota Sabang - Edy Putra Kelana; Rahmad Rahmad; Sri Murniyanti; Fitri Ernalis; Risky Novialdi (Departement of Mathematics Education, 2022)
Considering the fact that the practice of money politics is deeply embedded in people's lives, from the grassroots to the top, this complex issue must be taken seriously. An issue that seems trivial but has enormous negative implications for the development of democracy and law enforcement (Supremacy) in Indonesia. Money politics biases the political process. Due to money, it is difficult for elections to show the characteristics of honesty, fairness and fair competition. Elections like this end up creating a government that doesn't think about the fate and welfare of the people. The purpose of this study is to find out the urgency of political education in the province of Aceh. Case study: money politics in elections in the city of Sabang. The method used in this research is qualitative method. the survey results obtained 47% of respondents said they prioritized work, then 2% of respondents said they did not believe in election participants and prioritized work, there were 9% of respondents who did not believe in election participants, and there were 4% of respondents who did not believe in political parties and election participants, 27% of respondents did not believe in political parties and 2% of respondents said they were not registered and did not believe in political parties, and 9% of respondents were not registered on the final voter list (DPT).